World of popular entertainments : an edited volume of critical essays - Arrighi, Gillian; Emeljanow, Victor (Newcastle upon Tyne : Cambridge Scholars Pub., 2012)
"Despite the vibrant, complex, and ubiquitous nature of popular entertainments, the field has suffered from a lack of sustained academic attention. Nevertheless, popular entertainments have a global reach and a transnational significance at odds with the fact that the meaning and definition of both 'popular' and 'entertainment' remain widely contested. Since the late-nineteenth century, class-based prejudices in Western culture have championed the superiority of art and literature over the dubious and fleeting pleasures of 'entertainment.' Similarly, the term 'popular' has carried pejorative connotations, indicating something common and outside the conventional and highbrow productions of the purpose-built theatre house or concert hall"--Publisher.
pt. 1. Marvels and wonders -- pt. 2. Adaptation and preservation -- pt. 3. Leisure and tourism -- pt. 4. Sites of the popular -- pt. 5. The highbrow debate.
"This volume is the direct result of a conference which was hosted by the School of Drama, Fine Art and Music at the University of Newcastle, Australia, in June 2009"-- p. [ix].
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Entertainment events -- History and criticism; Amusements -- History and criticism; Popular culture -- History and criticism; Music-halls (Variety-theaters, cabarets, etc.) -- History and criticism; Theater -- History; Electronic books